2019
DOI: 10.1039/c9qo00300b
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-catalyzed sulfonylation of alkenylcyclobutanols with the insertion of sulfur dioxide through semipinacol rearrangement

Abstract: A photoredox-catalyzed sulfonylation of alkenylcyclobutanols with the insertion of sulfur dioxide through semipinacol rearrangement under visible light irradiation is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 142 publications
0
15
0
Order By: Relevance
“…Alkenyl cyclobutanols containing electron donating & electron withdrawing groups on the aromatic rings under standard reaction conditions affords the desired products in good yields (Scheme 46). [70] …”
Section: C−s Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkenyl cyclobutanols containing electron donating & electron withdrawing groups on the aromatic rings under standard reaction conditions affords the desired products in good yields (Scheme 46). [70] …”
Section: C−s Bond Formationmentioning
confidence: 99%
“…Alkenyl cyclobutanols containing electron donating & electron withdrawing groups on the aromatic rings under standard reaction conditions affords the desired products in good yields (Scheme 46). [70] The authors proposed the mechanism as shown in Figure 20. [71] At first, the aryl sulfonyl radical, generated from aryldiazonium salt and DABCO • (SO 2 ) 2 , reacts with the olefin of alkenyl cyclobutanol to provide a radical intermediate, which is further oxidized by the photocatalyst to form a cationic intermediate.…”
Section: Synthesis Of β-Sulfonated Ketonementioning
confidence: 99%
“…In 2019, a sulfonylation/semipinacol rearrangement has been established independently by several groups. Among these reactions, various types of reagents, such as ArN 2 BF 4 and (DABCO)$(SO 2 ) 2 , 39 ArSO 2 H, 40 and ArSO 2 Cl, 41 were used to generate arylsulfonyl radicals by means of photoredox-catalysis. Of note, electrochemical conditions have also been applied for the generation of arylsulfonyl radicals from either ArSO 2 NH 2 -NH 2 or PhSO 2 Na, 42,43 which provide mild and convenient protocols for the synthesis of b-sulfonated ketones.…”
Section: Allylic Alcoholsmentioning
confidence: 99%
“…Additionally, 4‐methyl‐2,6‐di‐tert‐butylphenol could only afford the corresponding product in 25% yield, which might be caused by its steric hindrance. In 2019, the Wu group [30b] designed a cascade of radical addition and semipinacol rearrangement. Aryl cyclopentanols gave higher yields (56–91%) than the less strained alkenylcyclopentanol (51%).…”
Section: C−x (X=b S P) Bond Formationmentioning
confidence: 99%